PERBEDAAN PENGARUH ANTARA VARIASI LATIHAN SERVIS ATAS MENGGUNAKAN KICK PAD DAN BOLA GANTUNG TERHADAP KETEPATAN SERVIS PUNGGUNG KAKI PADA CABANG OLAHRAGA SEPAK TAKRAW - PURBA, JOEN PARNINGOTAN; SILALAHI, EKA KARTIKA SILALAHI KARTIKA; PURBA, FRIKSON JONY; MANALU, RIZKI BASTANTA B.; NAINGGOLAN, ASER PAUL (LP2MTBM MAKARIOZ, 2022)
This study aims to determine the difference in the influence between the variations of upper serve exercises using kick pads and hanging balls on the accuracy of instep service in the sport of sepak takraw. This study was conducted on students of SMA Negeri 1 Bangko Pusako who participated in extracurricular activities of sepak takraw. Problem identification showed that there were several obstacles in the accuracy of serving, such as inaccurate contact of the ball on the foot, lack of eye-foot coordination, lack of effective form of exercise, limb stiffness, and weak support when performing top serve. The purpose of this study is to prove the influence of the two training models on the accuracy of the instep service in the sport of sepak takraw. This research is expected to provide benefits for sports teachers and students at SMA Negeri 1 Bangko Pusako, especially in improving the ability to serve in the game of sepak takraw. In addition, this research can be a reference for science in the teaching and learning process as well as a reference for other researchers who are interested in the problem of service accuracy in sepak takraw. This research is expected to make a practical contribution to sepak takraw coaches in choosing more effective training methods to improve the accuracy of the instep serve, especially for students who play as tekong.